2015
DOI: 10.11621/pir.2015.0410
|View full text |Cite
|
Sign up to set email alerts
|

Fear of childbirth in pregnant women: External and internal factors

Abstract: Fear of childbirth (FOC) is an important psychological problem that is studied worldwide because it affects the well-being of pregnant women. However, in Russia, this problem does not receive adequate attention among researchers. The purpose of the present study was to investigate the conditionality of fear of childbirth (FOC) in pregnant women by external and internal factors, which we assumed were the reasons for this fear. As external factors, we considered socio-demographic indicators (e.g., age, marital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“…(2,3) According to researches carried out in many countries, approximately 20 to 80 per cent of pregnant women experience differing levels of FoC, and the incidence of FoC has increased over time. (4) Researches demonstrate that approximately 25% of pregnant women suffer from a high level of FoC. (5) Pregnants personality traits and their psychological characteristics are effective on their thoughts, emotions and expectations in pregnancy.…”
Section: Background and Aimmentioning
confidence: 99%
See 1 more Smart Citation
“…(2,3) According to researches carried out in many countries, approximately 20 to 80 per cent of pregnant women experience differing levels of FoC, and the incidence of FoC has increased over time. (4) Researches demonstrate that approximately 25% of pregnant women suffer from a high level of FoC. (5) Pregnants personality traits and their psychological characteristics are effective on their thoughts, emotions and expectations in pregnancy.…”
Section: Background and Aimmentioning
confidence: 99%
“…This situation adversely affects the immune system of pregnants and the health of the fetus and chro-nic stress over the course of a few weeks may slow fetal development and result in future problems in the child. (4,7) In the literature, women with a stressful pregnancy period also have more FoC. (5,7) and when they can not cope with stress effectively, negative consequences of stress may threaten maternal and fetal health.…”
Section: Background and Aimmentioning
confidence: 99%
“…It has been found that women with primary TP often develop the phobia in adolescence and experience a stable course of symptomology (Hofberg & Brockington, 2000). While the exact content of the fear is not well‐studied, women with fears of childbirth often express anxiety about the wellbeing of their unborn child (Lopukhova & Kashshapova, 2015), fear of childbirth itself (Lopukhova & Kashshapova, 2015), and a fear of losing control during labour (Green & Baston, 2003; Lowe, 2000). A severe fear of childbirth can also be associated with suboptimal maternal labour and delivery experiences, including reporting more intense pain during delivery (Haines, Rubertsson, Pallant, & Hildingsson, 2012), increased likelihood of requesting an elective caesarean (Haines et al, 2012), a longer labour (Adams, Eberhard‐Gran, & Eskild, 2012) and more negative perceptions of childbirth (Haines et al, 2012) that persist even 1 year after the delivery (Nilsson, Lundgren, Karlström, & Hildingsson, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] According to the study of Fenwick et al ., fear of unknowns, lack of confidence in childbirth, internalization of negative narratives of other women, and birth pain are higher in women with the first experience of childbirth compared to those who had this experience. [ 9 ] There have so far been some studies in the field of reducing fear of childbirth such as classes to prepare for childbirth, relaxation, cognitive-behavioral, and educational interventions[ 10 11 12 13 ] which have been effective in reduction of fear of childbirth, but between 20% and 80% of pregnant women continue to experience some levels of childbirth fear, and the level of childbirth fear has increased over time[ 14 ] in a way that 83% of pregnant women had severe childbirth fear[ 15 ] in the study of Moasheri et al ., (2015) given that natural delivery is the best way of giving birth in most pregnant women, and approximately 85–90% of deliveries can be done naturally without any treatment intervention, and performing cesarean section surgery which according to the World Health Organization (WHO) is about 10%–15% acceptable is limited to cases where delivery is not possible through the natural channel and in general in condition when life of the mother and the fetus in the absence of surgical intervention is compromised. [ 16 ] However, according to interventions, the rate of delivery of cesarean delivery in Iran is still reported to be 3–4 times higher the global standard, and based on systematic review and meta-analysis of Azami-Aghdash et al .…”
Section: Introductionmentioning
confidence: 99%